2019
DOI: 10.1093/mnras/stz1281
|View full text |Cite
|
Sign up to set email alerts
|

Observation of narrow polar jets in the nascent wind of oxygen-rich AGB star EP Aqr

Abstract: Using ALMA observations of 12 CO(2-1), 28 SiO(5-4) and 32 SO 2 (16 6,10 -17 5,13 ) emissions of the circumstellar envelope of AGB star EP Aqr, we describe the morpho-kinematics governing the nascent wind. Main results are: 1) Two narrow polar structures, referred to as jets, launched from less than 25 au away from the star, build up between ∼ 20 au and ∼ 100 au to a velocity of ∼ 20 km s −1 . They fade away at larger distances and are barely visible in CO data. 2) SO 2 , SiO and CO emissions explore radial ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…Table 1 summarises its properties. There have been several recent investigations of the CSE around EP Aqr (Nhung et al 2015;Homan et al 2018;Tuyet Nhung et al 2019;Hoai et al 2019;Tuan-Anh et al 2019), most of them of the CO lines with ALMA. Tuan-Anh et al (2019) found jets extending from 25 to 1000 au.…”
Section: Properties Of Ep Aqrmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarises its properties. There have been several recent investigations of the CSE around EP Aqr (Nhung et al 2015;Homan et al 2018;Tuyet Nhung et al 2019;Hoai et al 2019;Tuan-Anh et al 2019), most of them of the CO lines with ALMA. Tuan-Anh et al (2019) found jets extending from 25 to 1000 au.…”
Section: Properties Of Ep Aqrmentioning
confidence: 99%
“…References. Gontcharov (2012) observations (Tuyet Nhung et al 2019;Homan et al 2018;Hoai et al 2019;Tuan-Anh et al 2019) which point at spiral arms embedded in a disc-like geometry, as seen nearly face-on. This paper has the following structure.…”
Section: Introductionmentioning
confidence: 99%
“…Evolved stars often feature a bipolar molecular outflow. A number of evolved stars at different stages of evolution and different orientations in space have been studied at DAP using observations of the high resolution continuum and line emissions from dust grains and gas molecules [8][9][10][11][12][13][14][15]. Methods to study and reconstruct in space axisymmetric radio sources (a common feature of young and old stars) have been developed to this effect [16,17].…”
Section: Evolved Starsmentioning
confidence: 99%
“…The high velocity streams are present in CO emission but weaker than in SiO emission (Figure 4), suggesting that they slow down and/or diverge at large distances from the star. These streams are very narrow (~10 o ), launched from less than 25 au from the star on the line of sight direction and build up between ~20 au and ~100 au to a velocity of ~ 20 km s −1 [3]. The mechanism governing the launching of the observed streams remains unknown.…”
Section: Ep Aqrmentioning
confidence: 99%
“…Recently, the availability of high angular resolution ALMA (Atacama Large Millimeter/sub millimeter Array) observations of several oxygen rich AGB stars like EP Aqr, R Dor, L 2 Pup and Mira Ceti have shed a new light on this issue [3][4][5][6]. However, the origin of these high velocities is still unclear.…”
Section: Introductionmentioning
confidence: 99%